The risk of pressure ulcers in a proned COVID population. Issue 4 (August 2022) - Challoner, Tom; Vesel, Teodora; Dosanjh, Amandeep; Kok, Kenneth
Abstract: The utilisation of prone positioning has been vital during the COVID-19 pandemic, however risks the development of anterior pressure ulcers. An observational study was performed to examine the prevalence of pressure ulcers in this population and define risk factors. Eighty-seven patients admitted to critical care were studied. Of 62 patients with >1 day in prone position, 55 (88.7%) developed anterior pressure ulcers, 91% of which were anterior. The most commonly affected site were the oral commisures (34.6%), related to endotracheal tube placement. Prone positioning (p < .001) and the number of days prone (OR 3.11, 95% CI 1.46–6.62, p = 0.003) were a significant risk factors in development of an anterior ulcer. Prone positioning is therefore a significant cause of anterior pressure ulcers in this population. Highlights: Prone positioning is commonly being employed for treatment of severe hypoxia in COVID-19 patients Positioning risks development of pressure ulcers on the head, neck and genitals Use of medical devices such as endotracheal and nasogastric tubes, and urinary catheters increase risk if not positioned correctly All attempts should be made to reduce risk as proning necessary for improving outcomes of patients